2012
DOI: 10.1016/j.atherosclerosis.2012.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Copper chelation by tetrathiomolybdate inhibits vascular inflammation and atherosclerotic lesion development in apolipoprotein E-deficient mice

Abstract: Endothelial activation, which is characterized by upregulation of cellular adhesion molecules and pro-inflammatory chemokines and cytokines, and consequent monocyte recruitment to the arterial intima are etiologic factors in atherosclerosis. Redox-active transition metal ions, such as copper and iron, may play an important role in endothelial activation by stimulating redox-sensitive cell signaling pathways. We have shown previously that copper chelation by tetrathiomolybdate (TTM) inhibits LPS-induced acute i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 28 publications
2
43
0
1
Order By: Relevance
“…In a recent study, TTM reportedly inhibited vascular inflammation and atherosclerotic lesion development in apolipoprotein-E deficient mice [47], raising the possibility that similar effects could also contribute to the cardiovascular responses to trientine. However, in this study, 10-weeks treatment with TTM induced significant lowering of circulating ceruloplasmin levels, raising the possibility that the reported findings could have been confounded by concomitant copper deficiency, as signaled by marked lowering of serum ceruloplasmin levels.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, TTM reportedly inhibited vascular inflammation and atherosclerotic lesion development in apolipoprotein-E deficient mice [47], raising the possibility that similar effects could also contribute to the cardiovascular responses to trientine. However, in this study, 10-weeks treatment with TTM induced significant lowering of circulating ceruloplasmin levels, raising the possibility that the reported findings could have been confounded by concomitant copper deficiency, as signaled by marked lowering of serum ceruloplasmin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac endothelial dysfunction observed in ApoE -/- (apolipoprotein E) knockout mice, prone to atherosclerosis, have been studied after the oral administration of TM for 10 weeks [270]. A specific reduction of bioavailable copper has been detected in both the serum (in the holo-ceruloplasmin form) and aorta, associated with a moderate decrease of both atherosclerotic lesions and accumulating macrophages [270].…”
Section: Copper and Angiogenic Diseasesmentioning
confidence: 99%
“…Cardiac endothelial dysfunction observed in ApoE -/- (apolipoprotein E) knockout mice, prone to atherosclerosis, have been studied after the oral administration of TM for 10 weeks [270]. A specific reduction of bioavailable copper has been detected in both the serum (in the holo-ceruloplasmin form) and aorta, associated with a moderate decrease of both atherosclerotic lesions and accumulating macrophages [270]. Specifically, TM-induced copper starvation in TNFα-treated human aortic endothelial cells has been shown to trigger the inactivation of NFκB and AP-1 pathways and reduced expression of ICAM1 and vascular cell adhesion molecule 1 [259].…”
Section: Copper and Angiogenic Diseasesmentioning
confidence: 99%
“…Copper is involved in critical processes including mitochondrial respiration and antioxidant capacity in the body [1]. Cellular copper levels must be tightly controlled because both copper accumulation and deficiency can induce cardiovascular disorders [2,3,4]. Many lines of evidences showed that high serum copper was associated with increased cardiovascular risks, for example, copper level of ischemic cardiomyopathy patients was higher than that of the healthy volunteers [5]; serum copper concentration was higher in rheumatic heart disease patients than in controls [6]; Serum copper level in subjects with acute decompensation of chronic heart failure was higher than that with chronic stable heart failure and serum copper was as a marker of inflammation in prediction of short term outcome in high risk patients with chronic heart failure [7].…”
Section: Introductionmentioning
confidence: 99%